A multi-institutional study to evaluate the effectiveness and safety of a supine MRI-based guidance system, the Breast Cancer LocatorTM, for breast conserving surgery in patients with nonpalpable breast cancer - Thill, Marc; Ghilli, Matteo; Roncella, Manuella; Kelling, Katharina; Fansa, Hisham; Golatta, Michael; Heil, Jörg; Haasteren, Viviane; Freitag, Amelie; Togawa, Riku; Sagona, Andrea; Rooney, Timothy B.; et al. (Annals of surgical oncology, 2025)
Background: The Breast Cancer LocatorTM (BCL) has been demonstrated to be a safe and effective guidance system for breast-conserving surgery (BCS) in patients with palpable breast cancer, but its effectiveness in patients with nonpalpable breast cancer has not been evaluated. Patients and Methods: Supine magnetic resonance imaging (MRI) images were used to generate (1) an interactive three-dimensional (3D) virtual image of the tumor in the breast and (2) a plastic bra-like form (BCL) that enabled the surgeon to place wires that bracketed the tumor volume. The primary objective was to determine the proportion of patients undergoing margin negative resections. Results: A total of 35 subjects were enrolled at 5 sites by 9 surgeons. In the 33 patients treated per protocol, 31 had margin negative resections (94%). All 31 patients with negative margins had negative margins on the primary lumpectomy specimen resected with BCL guidance. Additional shave margins were taken in 4 of the 31 patients; no cancer was present in the shaves. A total of 25 patients had invasive ductal carcinoma, 7 invasive lobular carcinoma, and 3 ductal carcinoma en situ (DCIS). The mean tumor diameter was 3.1 cm and specimen volume was 56 ml. The median actual/targeted specimen volume ratio was 1.18. There was no significant difference in preop versus postop Breast-Q scores: 66.5 versus 64.0, p = 0.58. Surgeons judged the BCL guidance system to be easy to use in 91% of cases. Conclusions: The BCL guidance system enabled surgeons to do precise BCS: margin negative resections were obtained in a high proportion of cases, resected specimen volumes were relatively low, and patients’ satisfaction with their breasts was not adversely effected by surgery.